Amyotrophic Lateral Sclerosis - Malik, Rabia; Lui, Andrew; Lomen-Hoerth, Catherine (Seminars in Neurology, 2014)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder affecting 20,000 to 30,000 people in the United States. The mainstay of care of patients affected by this disease is supportive and given the multifaceted nature of their needs is provided most efficiently through multidisciplinary clinics that have shown to prolong survival and improve quality of life. The authors discuss in detail evidence-based management of individuals affected by this condition.
Keywords: amyotrophic lateral sclerosis; orthoses; wheelchair; exercise; respiratory; nutrition; spasticity